PREFIKS NEGATIF DALAM BAHASA INGGRIS - Setyo Untoro (Universitas Nasional, 2016)
This research is aimed at describing the form, meaning, and use of negative prefixes in English. The research usesdescriptive method. The results show that negative prefixes in English can be attached to adjectives, verbs, adverbs,and nouns. An English base or stem may be attached by one or two negative prefixes with similar or differentmeaning. The addition of a negative prefixe to its base or stem may change or may not change its word class.Keywords: negative prefix, adjective, verb, adverb, noun.